Black Stars – Contextualizing the Rise of blaxTARLINES: Contemporary art of the late 20th to the early 21st Centuries in Ghana. Issue 1 (2nd January 2019) - Kwami, Atta
Abstract : Several identifiable events have propelled local and international interest in contemporary visual art practices in Ghana in the 21st century. These include international exhibitions and art fairs, workshops, symposia and the emergence of significant projects spaces and artists foundations. Much of these developments occurred in Ghana from 1999 to the present day. The Internet, mobile phones, and social media make it possible for young artists to bypass, or subvert, established institutions. The outcome has been largely positive in bringing visiting artists, museum curators, and other art-world notables to engage directly with contemporary Ghanaian artists and seek out new talent. However, despite these formal platforms that have served as crucibles or catalysts for current artistic practice in Ghana, the practitioners themselves have, to a large extent, remained self-reliant. As individual artists may be considered institutions in their own right, it is not surprising that some have established their own art centers: Ablade Glover's Artists Alliance Gallery, Accra; Kofi Setordji's ArtHAUS; and Kati Torda's Sun Trade Beads, Accra, and the Studio. These new developments have exposed Ghanaian contemporary artists to new audiences. A plethora of related activities in fashion, film, and photography have also received widespread attention. My essay carries out case studies of five artists associated with blaxTARLINES KUMASI: Dorothy Amenuke, Edwin Bodjawah, Bernard Akoi-Jackson, Patrick Tagoe-Turkson, and Ibrahim Mahama, who represent the cutting edge of new Ghanaian interactions with the global contemporary.